ASSOCIATION OF PATHOGENIC FUNGI WITH SHEATH MITE, STENEOTARSONEMUS SPINKI INFESTATION IN RICE - MUTTHURAJU, G.P.; SRINIVASA, N.; GIRISH, R.; RAVICHANDRA, N.G.; PRASAD, G.R. GURU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The association of pathogenic fungi with grains from sheath mite (Steneotarsonemus spinki Smiley) infestation in fifteen rice entries grown under aerobic and normal puddled conditions was ascertained during kharif2009 and summer 2010 in Mandya district of Karnataka. Seven species of pathogenic fungi namely, Alternaria sp., 4spergillus flaw's, A. niger, Curvularia sp.. Drechs/era sp., Fusarium sp. and Pvricu/aria oryzae were recovered from discoloured (chaffy or tilled) erains from sheath mite infested rice fields. More of grain samples from summer crop harboured pathogenic fungi compared to samples from kharif season crop. Also, the pathogenic fungi were more prevalent in grain samples from aerobic situations compared to those from normal puddled crop.